2023
DOI: 10.3389/fnagi.2022.1055172
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional connectivity of the frontostriatal circuits in type 2 diabetes mellitus

Abstract: BackgroundType 2 diabetes mellitus (T2DM) is a metabolic disorder associated with an increased incidence of cognitive and emotional disorders. Previous studies have indicated that the frontostriatal circuits play a significant role in brain disorders. However, few studies have investigated functional connectivity (FC) abnormalities in the frontostriatal circuits in T2DM.ObjectiveWe aimed to investigate the abnormal functional connectivity (FC) of the frontostriatal circuits in patients with T2DM and to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 87 publications
0
2
0
Order By: Relevance
“…The caudate acts one of the hubs in frontostriatal circuits that have been implicated in behavior ( Ji et al, 2018 ). Previous study indicated that deficits in prefrontal-striatal sensorimotor loops involving the caudate nucleus might be the neuropathological basis of motor and sensory dysfunction in T2DM ( Fu et al, 2022 ). And these decreased connectivities might underlie certain abnormalities that occur in cognitive and emotional disorders ( Barber et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…The caudate acts one of the hubs in frontostriatal circuits that have been implicated in behavior ( Ji et al, 2018 ). Previous study indicated that deficits in prefrontal-striatal sensorimotor loops involving the caudate nucleus might be the neuropathological basis of motor and sensory dysfunction in T2DM ( Fu et al, 2022 ). And these decreased connectivities might underlie certain abnormalities that occur in cognitive and emotional disorders ( Barber et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some studies indicated that individuals with diabetes were more likely to develop anxiety disorders ( Buchberger et al, 2016 ; Cobham et al, 2020 ; Majidi et al, 2015 ). Abnormal blood glucose may lead to changes in brain function and metabolism including hippocampal atrophy, prefrontal cortex dysfunction, and neurotransmitter imbalance ( Fu et al, 2022 ; Zhang et al, 2021 ). Moreover, strict self-management requirements for diet and exercise may also lead to abnormalities in diabetic patients' emotional and cognitive functions.…”
Section: Introductionmentioning
confidence: 99%